(untitled) (Journal of the College of Basic Education, 2022)
The current research aimed at measuring the emotional innovation of educational counselors, and the research sample consisted of (400) educational counselors, and the two researchers used the emotional innovation measure that was adopted for this purpose after it was presented to a group of experts and arbitrators and extracted the psychometric characteristics of it, and the two researchers used statistical methods: the test The t-test for one sample and two independent samples, Pearson’s correlation coefficient, and Cronbach’s alpha equation. The results showed a good level of emotional innovation among educational counselors. The research came out with a set of recommendations and proposals.